Spatial distribution of microplastic concentration around landfill sites and its potential risk on groundwater. (August 2021) - K, Manikanda Bharath; Natesan, Usha; R, Vaikunth; R, Praveen Kumar; R, Ruthra; S, Srinivasalu
Abstract: Plastic plays a major role in today's human life; moreover, it becomes a part of our life, yet it is a most challenging threat for the freshwater ecosystems in the future. The present study identifies, characterizes, and quantifies the microplastics in groundwater samples around Perungudi and Kodungaiyur municipal solid waste dumpsites in South India. To evaluate and assess the microplastic abundance, characteristics (composite, size, colour, shape, and surface morphology), detection methods of plastic particles, and potential risk factors from the absorption of microplastic in groundwater. Further, the microplastic particle classification was performed using LB-340 Zoom Stereo Microscope with LED Illumination, ATR-FTIR fitted with SEM with EDX analyzer. The groundwater samples (n = 20) were found contaminated with microplastic particles in the range of 2–80 items/L with coloured particles, white (38%), black (27%), green (8%), red (18%), blue (6%), and yellow (2%). The polymer type was found to occur in the following order: nylon (70%), pellets (18%), foam (6%), fragments (3%), fibers/PVC (2%), and polythene (1%). In both sampling sites, 90% of microplastics are derived from the buried plastics and waste fragmentation which are predominantly of polypropylene (PP), polystyrene (PS). Micro and nano plastics abundance in groundwater is of paramount importance as it has a major impact on human health. This study throws light on the characteristics and quantification of the microplastics in groundwater that initiates further research by which microplastics enter into the environment. Graphical abstract: Image 1 Highlights: Microplastics have found in groundwater samples around the solid waste landfills. Microplastics abundance ranges from different sources 2 to 80 items/L. The number of microplastics increased with the decreasing of particle size less than 500 μm. The multi-analytical characteristics and assessing the potential risk of microplastic to human in groundwater developed.